TUBUH, SUBJEK SEKSUAL, DAN KEKUASAAN DALAM NOVEL TELEMBUK: DANGDUT DAN KISAH CINTA YANG KEPARAT KARYA KEDUNG DARMA ROMANSHA - Santoso, Joko (Balai Bahasa Jawa Timur, 2019)
Women's bodies as sexual objects are always in power relations. In Telembuk Dangdut dan Kisah Cinta yang Keparat, the characters of Diva and Mak Dayem are the representations of women's bodies as well as sexual objects in the power relation circle. This study aims to illustrate how women (Diva and Mak Dayem) compete with power by trying to make their bodies as sexual subjects in the novel Telembuk. The theory used in this study was the Power of Discourse theory proposed by Michel Foucault. According to the type of data, this study was a qualitative research. The data source was Kedung Darma Romansha?s novel Telembuk: Dangdut dan Kisah Cinta yang Keparat published in 2017. This study used discursive formation method to analyse the data. The results of this study were 1) the metaphysical body becomes the strategy of telembuk women to utter anti-power, 2) telembuk as a woman strategy to be a sexual subject.